Characterization of a chloroquine‐induced canine model of pruritus and skin inflammation. Issue 2 (27th November 2019) - Blubaugh, Amanda; Denley, Tara; Banovic, Frane
Abstract : Background: Chloroquine (CQ) is a prototypical systemic and intradermal pruritogen for histamine‐independent (nonhistaminergic) itch in mice and humans. The predictive validity of this model is poorly documented in dogs. Hypothesis/Objective: To determine pruritogenic and inflammatory effects of systemic and i.d. CQ injections in healthy dogs. Animals: Ten healthy purpose‐bred laboratory beagles. Methods and materials: All dogs were randomized to receive i.d. (200 and 400 µg/site), intravenous (2 mg/kg) and subcutaneous (3 mg/kg) CQ injections. Dogs were video‐recorded for 30 min after i.d. injections and for 300 min after i.v. and s.c. injections. Buffered saline injections served as controls for each route. Global wheal scores were evaluated at 30 min post‐i.d. injection by a blinded investigator. Results: All dogs showed wheal and erythema at the CQ i.d. injection sites; global wheal scores of each CQ concentration were significantly increased compared to placebo ( P ≤ 0.05). Blinded evaluation revealed no significant increase in generalized pruritic behaviour (pruritic seconds) after i.v. or s.c. administration of CQ. Intradermal injections induced mild localized acute pruritic behaviours at the site of injections at 200 µg ( P = 0.06) and 400 µg ( P = 0.27) CQ in dogs. Conclusion and clinical significance: To the best of the authors' knowledge, this is the first report which shows that i.d. CQ injections may induce acute inflammation in healthy dogs. By contrast to the systemic CQ‐induced pruritus reported previously in healthy mice and dogs, no significant pruritic behaviours were observed after CQ injection, regardless of the route of administration. Abstract : Background – Chloroquine (CQ) is a prototypical systemic and intradermal pruritogen for histamine‐independent (nonhistaminergic) itch in mice and humans. The predictive validity of this model is poorly documented in dogs. Hypothesis/Objective – To determine the pruritogenic and inflammatory effects of systemic and intradermal CQ injections in healthy dogs. Conclusion and clinical significance – To the best of the authors' knowledge, this is the first report which shows that i.d. CQ injections may induce acute inflammation in healthy dogs. By contrast to the systemic CQ‐induced pruritus reported previously in healthy mice and dogs, no significant pruritic behaviours were observed after CQ injection, regardless of the route of administration. Résumé: Contexte: La chloroquine (CQ) est un pruritogène intradermique et systémique prototypique pour les démangeaisons indépendante de l'histamine (non‐histaminergiques) chez la souris et l'homme. La validité prédictive de ce modèle est faiblement documentée chez le chien. Hypothèses/Objectifs: Déterminer les effets pruritogènes et inflammatoires d'injections intradermiques et systémiques de CQ chez des chiens sains. Sujets: Dix beagles de laboratoire sains. Matériels et methods: Tous les chiens ont été répartis au hasard pour recevoir des injections de CQ intradermiques (200 and 400 μg/site), intraveineuses (2 mg/kg) et sous cutanées (3 mg/kg). Les chiens ont été enregistrés par vidéo pendant 30 min après injections i.d. et pendant 300 min après i.v. et s.c. Des injections de solution saline ont servi de contrôle pour chaque voie. Les scores lésionnels ont été évalués à 30 min post injection i.d. par un investigateur en aveugle. Résultats: Tous les chiens ont montré une papule et un érythème aux sites d'injection i.d. de CQ; les scores lésionnels étaient significativement augmentées comparé au placebo (P ≤ 0.05). Une évaluation en aveugle n'a révélé aucune augmentation significative du comportement de prurit généralisé (secondes prurigineuses) après injections i.v. ou s.c. de CQ. Les injections intradermiques ont induit du prurit aigu localisé modéré aux sites d'injections à 200 μg ( P = 0.06) et 400 μg ( P = 0.27) CQ chez les chiens. Conclusion et importance Clinique: A la connaissance des auteurs, ceci est la première description qui montre que les injections i.d. de CQ peuvent induite une inflammation aiguë chez les chiens sains. Par contraste avec le prurit induit par CQ systémique précédemment rapporté chez le chien et la souris, aucune comportement de prurit significatif n'a été observé après les injections de CQ, quelques soit la voie d'administration. Resumen: Introducción: la cloroquina (CQ) es un pruritógeno prototípico sistémico e intradérmico para inducir picor independiente de histamina (no histaminérgica) en ratones y humanos. La validez predictiva de este modelo está poco documentada en perros. Hipótesis/Objetivo: determinar los efectos pruritogénicos e inflamatorios de la inyección sistémica e i.d. de CQ en perros sanos. Animales: diez perros sanos de raza Beagle de laboratorio. Métodos y materiales: todos los perros fueron asignados al azar para recibir inyecciones de CQ vía i.d. (200 y 400 μg/sitio), inyecciones intravenosas (2 mg/kg) y subcutáneas (3 mg/kg). Los perros fueron grabados en video durante 30 minutos después de las inyecciones vía i.d. inyecciones y durante 300 minutos después de inyecciones vía i.v. y s.c. Las inyecciones de solución salina tamponada sirvieron como controles para cada vía de administración. Las valoraciones globales de pápulas se evaluaron a los 30 minutos tras inyección vía i.d. por un investigador sin conocimiento del tipo de administración. Resultados: Todos los perros mostraron pápulas y eritema en los lugares de inyección de CQ i.d; los valores globales de pápulas de cada concentración de CQ aumentaron significativamente en comparación con el placebo ( P ≤0, 05). La evaluación por método ciego no reveló un aumento significativo en el comportamiento de prurito generalizado (segundos con prurito) después de administraciñon de CQ vía i.v. o s.c. Las inyecciones intradérmicas indujeron comportamientos pruríticos agudos localizados leves en el sitio de las inyecciones a 200 μg ( P = 0, 06) y 400 μg ( P = 0, 27) CQ en perros. Conclusión e importancia clínica: A entender de los autores, este es el primer artículo que muestra que las inyecciones de CQ vía i.d. pueden inducir inflamación aguda en perros sanos. En contraste con informes previos de inducción de prurito sistémico tras la administración de CQ en ratones y perros sanos, no se observaron comportamientos pruríticos significativos después de la inyección de CQ, independientemente de la vía de administración. Zusammenfassung: Hintergrund: Chloroquine (CQ) ist ein prototypisches systemisches und intradermales Pruritogen für Histamin‐unabhängigen (nicht‐histaminergischen) Juckreiz bei Mäusen und Menschen. Der Vorhersagewert dieses Modells ist bei Hunden noch wenig dokumentiert. Hypothese/Ziel: Eine Bestimmung der pruritogenen und entzündlichen Auswirkungen von systemischen und i.d. CQ Injektionen bei gesunden Hunden. Tier: Zehn gesunde Zweck‐gezüchtete Laborbeagles. Methoden und Materialien: Alle Hunde wurde randomisert, um i.d. (200 und 400 μg/Stelle), intravenös (2 mg/kg) und subkutan (3 mg/kg) CQ Injektionen zu erhalten. Die Hunde wurden nach den i.d. Injektionen 30 Minuten lang und nach i.v. und s.c. Injektionen 300 Minuten lang auf Video aufgenommen. Eine gepufferte Kochsalzlösung diente als Kontrolle für jede Art der Verabreichung. Gesamte Quaddelgrößen wurden 30 Minuten nach der i.d. Injektion von einem geblindeten Untersucher beurteilt. Ergebnisse: Alle Hunde zeigten Quaddeln und Erythem an den i.d. CQ Injektionsstellen; die Gesamtgrößen der Quaddeln waren bei jeder CQ Konzentration im Vergleich zu Plazebo signifikant größer ( P ≤ 0, 05). Eine geblindete Untersuchung zeigte keine signifikante Erhöhung des allgemeinen Juckreizverhaltens (juckende Sekunden) nach i.v. oder s.c. Administration von CQ. Intradermale Injektionen induzierten ein mildes akutes Juckreizverhalten an den Injektionsstellen mit 200 μg ( P = 0, 06) und 400 μg ( P = 0, 27) der Hunde. Schlussfolgerung und klinische Bedeutung: Nach bestem Wissen der Autoren handelt es sich hierbei um den ersten Bericht, der zeigt, dass i.d. CQ Injektionen eine akute Entzündung bei gesunden Hunden auslösen können. Im Kontrast zum systemischen CQ‐induzierten Juckreiz, der bisher bei gesunden Mäusen und Hunden beschrieben war, wurde kein signifikantes Juckreizverhalten nach den QC Injektionen beobachtet, egal bei welcher Form der Administration. 摘要: 背景‐氯喹(CQ)是: 种典型的全身和皮内瘙痒原, 用于小鼠和人类的组胺无关(非组胺能)瘙痒。这个模型的预测有效性在犬身上没有得到充分证明。 假设/目的: 确定全身和皮内注射CQ对健康犬的致痒和炎症作用。 动物: 10只健康的实验用小猎犬。 方法和材料: 所有的犬被随机分配接受皮内注射(200和400 μg /点), 静脉注射(2mg/kg)和皮下注射(3mg/kg)CQ。给犬皮内注射30分钟后, 以及静脉和皮下注射300分钟后拍摄录像。每种方式都用缓冲盐水注射作为对照。在皮内注射30分钟后, 调查人员进行盲法风疹整体评分。 结果: 所有犬在注射部位都有风疹和红斑;各CQ浓度的风疹整体评分较安慰剂组显著升高(P≤0.05)。盲法评估显示, CQ在静脉或皮下给药后, 全身瘙痒行为(次级瘙痒)没有明显增加。给犬皮内注射200μg (P = 0.06)和400μg (P = 0.27) CQ时, 引起了轻微的局部急性瘙痒行为。 结论和临床意义: 作者所知, 这是第一份研究注射CQ可能引起健康犬急性炎症的报告。与之前CQ导致健康小鼠和犬全身性瘙痒的报道相比, 无论给药途径如何, 注射CQ后均未观察到明显的瘙痒行为。 要約: 背景: クロロキン(CQ)は、マウスおよび人のヒスタミン非依存性(非ヒスタミン作動性)掻痒に対するプロトタイプの全身および皮内プルトゲンである。このモデルの予測的妥当性は、犬ではほとんど文書化されていない。 仮説/目的: 本研究の目的は、健常犬に対するCQの全身および皮内注射における起痒性および炎症性効果を判定することであった。 被験動物: 10頭の研究目的で飼育された実験健常ビーグル。 材料と方法: すべての犬はランダムに皮内(200および400μg/部位)、静脈(2 mg / kg)および皮下(3 mg / kg)のCQ注射を受けた。犬を、皮内注射後30分間、そして皮下および静脈注射後300分間ビデオ録画した。緩衝生理食塩水注射は、各ルートのコントロールとして機能した。全膨疹スコアを盲検者による皮内注射30分後に評価した。 結果: すべての犬は、CQ皮内注射によって膨疹および紅斑を示した。また、各CQ濃度の全膨疹スコアは、プラセボと比較して有意に増加した(P≤0.05)。盲検評価では、CQの静脈または皮下投与後の全身性掻痒行動(掻痒秒数)に有意な増加は認められなかった。200μg(P = 0.06)および400μg(P = 0.27)CQによる皮内注射は、犬の注射部位に軽度の局所急性掻痒行動を誘発した。 結論と臨床的意義‐著者の知る限り: 本研究はCQによる皮内注射が健常犬に急性炎症を引き起こす可能性があることを示した最初の報告である。健常マウスおよび犬で以前に報告された全身性CQ誘発性掻痒とは対照的に、投与経路に関係なく、CQ注射後に有意な掻痒行動は観察されなかった。 Resumo: Contexto: A cloroquina (CQ) é um protótipo de pruritógeno sistêmico e intradérmico para prurido independente de histamina (não histaminérgico) em camundongos e seres humanos. O valor preditivo desse modelo é pouco documentado em cães. Hipótese / Objetivo: Determinar os efeitos pruritogênicos e inflamatórios de injeções sistêmicas e intradérmicas de CQ em cães saudáveis. Animais: Dez beagles de laboratório saudáveis. Métodos e materiais: Todos os cães foram randomizados para receber injeções de CQ por via intradérmica (200 e 400 μg / local), intravenosa (2 mg / kg) e subcutânea (3 mg / kg). Os cães foram gravados por vídeo durante 30 minutos após a administração de injeções intradérmicas e durante 300 minutos após administração intravenosa e subcutânea. Injeções de solução salina tamponada foram utilizadas como controle para cada via. Os escores globais de pápula foram avaliados por um investigador cego 30 minutos após a administração da injeção intradérmica. Resultados: Todos os cães apresentaram pápula e eritema nos locais de injeção intradérmica de CQ; os escores globais de pápula de cada concentração de CQ aumentaram significativamente em comparação com o placebo (P ≤ 0, 05). A avaliação cega não revelou aumento significativo no comportamento de prurido generalizado (tempo de prurido em segundos) após administração intravenosa ou subcutânea de CQ. As injeções intradérmicas induziram comportamentos pruriginosos agudos localizados e leves em cães no local das injeções de CQ em concentrações de 200 μg (P = 0, 06) e 400 μg (P = 0, 27). Conclusão e significância clínica: De acordo com os conhecimentos dos autores, este é o primeiro relatório que mostra que injeções intradérmicas de CQ podem induzir inflamação aguda em cães saudáveis. Em contraste com o prurido sistêmico induzido pela CQ relatado anteriormente em cães e ratos saudáveis, não foram observados comportamentos pruriginosos significativos após a injeção da CQ, independentemente da via de administração.